Foodborne Pathogens: The Antimicrobial Resistance from Farm to Fork - Gabriel Augusto Marques Rossi; Laryssa Freitas Ribeiro; Marita Vedovelli Cardozo (Pathogens)
Foodborne diseases pose a major threat to global public health and contribute substantially to economic losses, increased healthcare expenses, negative effects on child development, reduced productivity, and losses in international trade [...]